ADVANTAGES, DISADVANTAGES AND PROSPECTS OF IMPLEMENTING A PIECE-RATE FORM OF PAY AT THE INDUSTRIAL ENTERPRISE ENVIRONMENT - NESTEROVA, SVITLANA; SURMAI, DANYLO (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The paper considers the conditions of expediency of using the piece-rate form of pay in the modern industrial environment. The necessity to ensure implementation of the motivational and stimulating role of the pay system is noted, as both business efficiency and employee motivation depend on this choice. The extensive use of piece-rate form of pay at industrial enterprises is related to its proven advantages, the main of which is the obvious relationship between production output and wages. This stimulates to increase individual employee productivity rate and efficiency the production system as a whole. The reason for the piece-rate form of pay to be promising to consist in its flexibility and ability to transform depending on the specifics of production environment and conditions of labour organization. Emphasized that despite mentioned advantages, implementation of piece-rate form of pay has its own certain limitations and risks. Specifically, it does not natively support accounting for a quality parameters of production, may lead to violation of production process synchronicity requirement and omit compliance to the norms of material consumption. Is determined that while choosing forms and systems of pay, it should be clearly understood that the development of an effective such system for successful monetary motivation of employees at the enterprise environment is an extremely complex task and depends on multiple factors, even if we take into consideration industrial enterprises only.